Utilization of Media Social in Marketing of Processed of Fisheries Product at Sanga-Sanga District - Gusti Haqiqiansyah; Qoriah Saleha; Rahmasari Rahmasari (Jurnal Perikanan dan Kelautan, 2021)
Social media presence become a basic necessity for the community. Almost all levels of society use this technology. Likewise in the business world. Business actors must race to introduce their products. The use of social media is one of the solutions to speed up business promotion. The purpose of research to determine the perceptions and types of use of social media by processed fisheries business actors in Sanga Sanga District. Methods of collecting data were observation and interviews. Samples were taken by means of a census of 11 people. Data were tabulated and analyzed descriptively. To measure the level of perception using a Likert scale. The results showed that the level of perception was in the moderate category (score reached 27.91), meaning that the use of social media in business activities was still not optimal. The types of social media used are Facebook (81.82%), whatsAap (54.55%) and youtube (18.18%).